A Bidirectional Mendelian Randomization Study of Causal Relationships Between Migraine and White-Matter Structural Connectivity - Tong D; Zhang X; Xiao Z; Taothong S; Teeravarunyou P; Wu W; Wu S; Chen N; Tao S; Zhou J; Song Q; Liang F; et al. (Journal of Pain Research, 2025)
Dan Tong,1,2,* Xinyue Zhang,1,2,* Zhiyong Xiao,1,3,* Supattra Taothong,1,2 Prapawee Teeravarunyou,1,2 Wanxia Wu,1,2 Sai Wu,1,2 Nuo Chen,1,2 Siyuan Tao,1,2 Jun Zhou,1,2 Qian Song,4 Fanrong Liang,1,2 Zhengjie Li1,2,4 On behalf of International Headache Genetics Consortium (IHGC)1Acupuncture and Tuina School, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 2Key Laboratory of Acupuncture for Senile Disease (Chengdu University of TCM), Ministry of Education, Chengdu, Sichuan, People’s Republic of China; 3Sichuan Jinxin Xinan Women’s & Children’s Hospital (Bisheng), Chengdu, People’s Republic of China; 4National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhengjie Li, Email lzjbenjamin@163.comObjective: This study aims to investigate the potential causal relationship between migraine and white matter (WM) structural connectivity using genetic data and the Mendelian randomization (MR) analyses method.Methods: Genome-wide association study (GWAS) summary statistics for migraine (48,975 cases/540,381 controls) and 206 WM structural connectivity related imaging-derived phenotypes (IDPs) (26,333 samples) were collected. Based on instrumental variables (IVs) selected from the GWAS summary statistics, the bidirectional two-sample MR analyses were conducted to infer bidirectional causal associations between migraine and WM structural connectivity. The inverse variance-weighted (IVW) method served as the primary approach for analyzing causality.Results: In the forward MR analysis, it was found that migraine had a significant effect on right hemisphere somatomotor network to amygdala WM structural connectivity (IVW-derived β = 0.11, 95% CI = [0.04, 0.17], p = 1.02e-03, FDR p = 0.04). While in the reverse MR analysis, no causal link was detected between WM structural connectivity and migraine.Conclusion: This study provides genetic evidences for a causal relationship between migraine and WM structural connectivity. These findings provide new perspectives for the understanding of neuropathology and symptomatology in migraine and might provide a potential therapeutic target for future migraine treatment research.Keywords: migraine, white matter structure connectivity, imaging-derived phenotype, neuroimaging, causal relationship, Mendelian randomization